Rectangular Illumination Based on Diffuse Reflective Off-Axis Surface - Zhen-Min Zhu; Xiang Sun; Bo Peng (IEEE Photonics Journal)
Diffuse reflective LED lighting system is widely used in many areas, while rectangular illumination is also widely used in various lighting fields because of its regular lighting shapes, but traditional diffuse reflection method can only produce circular spot. This paper first introduced rectangular illumination into design of the diffuse reflective surface, combined the merits of both. A mathematical model of a diffuse reflective off-axis surface based on a single LED chip, desired value of the target plane and energy conservation is established and the shape of the illumination facula is used as the constraint condition. By solving the nonlinear equations, a number of two-dimensional (2-D) curves are obtained and combine these 2-D curves into off-axis surface. The results show that the shape of the illumination facula is close to the standard rectangle, and the efficiency and the uniformity of illumination is higher than traditional diffuse reflectors.